(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
One of the most important basic platforms in a smart city for preventing recurrent manhole cover accidents is an intelligent manhole cover management system. Manhole cover removal, loss, and injury endangers people’s safety, which is contrary to the aim of smart cities. This article describes an intelligent manhole cover management system (IMCS) for smart cities that is based on edge computing. Each manhole cover has its own radio frequency identification tag with tilt and vibration sensors, and communication is done through a narrow-band Internet of things. Meanwhile, based on the collected data, edge computing servers communicate with appropriate management employees through mobile devices. The effectiveness of the proposed IMCS was shown in a demonstration application in Hangzhou’s Xiasha District. It halved the repair time, possibly improving the safety of both humans and manhole covers.